Chapter 10 Final thoughts Heritage as a dimension of collectivity and belonging - Whitehead, Christopher (Taylor & Francis, 2019)
This final chapter takes up these questions, mining some of our ethnographies for support. One of these is the basis for a short diversion to a Turkish coffeehouse in what used to be the edge of West Berlin. This is a marginal story that turns out to be central, allowing us to suggest that among the multiple Europes circulating and bickering in the air around us, there are still some others yet to be brought into sight. After this, we close the book with some practical comments about what, in this time of perceived crisis, should be done to re-orient ideas of the European past at the level of heritage practice.